Field notes contributed by Pearl Knoop, spring 1983 - Knoop, Pearlet al (1983)
Spring report of birds found around Marble Rock contributed by Pearl Knoop. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1983. Epson - sheet feed